NMDAR autoantibodies in psychiatric disease - An immunopsychiatric continuum and potential predisposition for disease pathogenesis - Niels Hansen (Journal of Translational Autoimmunity, 2022)
N-Methyl-d-Aspartate-receptor (NMDAR) antibody encephalitis is a disease discovered two decades ago. Our knowledge about it has recently deepened dramatically. However, the significance of NMDAR antibodies in psychiatric disease cannot be determined if there are no clear indications of brain inflammation or an autoimmune encephalitis mediated by NMDAR antibodies. Furthermore, the long-term interaction and connection between these two disease entities are unclear. In this paper we aim to elucidate the relationship between these disease entities. We propose two distinct models that explain the on the one hand a condition in which a minor inflammatory state as in psychiatric disease culminates in a severe state of inflammation characterized by NMDAR encephalitis. On the other hand, we postulate a model in which an NMDAR encephalitis might later create favorable conditions for inducing psychiatric disease. These models should be kept in mind for further investigations examining the long-term outcome of NMDAR autoantibody immunity in the brain and its functions.